Electrochemically active polyimides containing hydroxyl-functionalized triphenylmethane as molecular sensors for fluoride anion detection. (1st September 2020) - Chiriac, Adriana-Petronela; Butnaru, Irina; Damaceanu, Mariana-Dana
Abstract: In the challenging pursuit of endowing the high performance polyimide systems with efficient responsive side chains, we have designed and synthesized a series of four molecular sensors containing OH group grafted on triphenylmethane (TPM) core as receptor for the fluoride anion. The sensing platforms were obtained by solution polycondensation reaction of a new TPM-based diamine bearing the OH receptor with four ether-dianhydrides containing different substituents, such as 9, 9-diphenyl-fluorene, cyclohexane, isopropylidene or hexafluoroisopropylidene. These structural elements are meant to increase the flexibility of the polyimide backbones, as well as solubility and processing ability from easy accessible solvents, while preserving a high thermal stability. Since TPM-OH based polyimides have not been studied yet with regard to their photo-optical and electrochemical features, we have performed a systematic study which highlighted a complex behaviour in strong dependence on the surrounding environment. The UV–Vis absorption and ﬂuorescence spectra evidenced the occurrence of solute-solvent interactions which are responsible for unusual pink colour of these polyimides. Meanwhile, intermolecular hydrogen bonding evolved in solid state. These features promoted a redox behaviour contingent on the polyimides ability to generate the keto tautomer. For the first time in the case of polyimides, spectroscopic and electrochemical responses to fluoride anion were thoroughly analysed by fluorescence and cyclic voltammetry, besides the already known UV–Vis and 1 H NMR spectroscopies. Clear changes occurred in the presence of the fluoride anion (with tetrabuthylammonium as the counter ion), allowing us to discriminate it by other anions. The sensing recognition capability was demonstrated by colour change from pink to yellow, fluorescence enhancement and variation from blue to yellowish-green, disappearance of the OH proton signature and easier oxidation in the presence of fluoride anions. Since the acid CH group of TPM core is indirectly entangled in the sensing mechanism of the fluoride anion, different concurrent recognition principles may be considered. Even complex, the sensing behaviour of the understudy polyimides proved that a single OH group/monomeric TPM unit is appropriate for efficient fluoride anion recognition. Graphical abstract: Image 1 Highlights: Electrochemically active polyimides containing hydroxyl-functionalized triphenylmethane are developed. Their redox features highlighted for the first time are contingent on the physical state. The occurrence of polymer-solvent interactions and intermolecular H bonding in solid state is evidenced. The sensing of Fˉ anion is demonstrated by cyclic voltammetry, fluorescence, UV-Vis absorption and 1 H-NMR spectroscopies. The indirect involvement of CH unit from TPM core in the recognition of Fˉ anion leads to a complex sensing mechanism.